Two new species of Eperua (Leguminosae, Detarioideae, Detarieae) from the Amazon and Cerrado Biomes discovered in a botanical garden and a backyard - Fortes, Elenice A.; Da Silva, Guilherme S.; Mansano, Vidal F. (Phytotaxa, 2023)
In this study, we describe two new species of Eperua, E. cerradoensis and E. manausensis. Eperua cerradoensis is the first species of the genus described from the Cerrado Biome (Brazil); all other 16 species, including the other new species described here E. manausensis, are endemic to the Amazon region (Amazon basin and the Guiana Shield). Both species have short and erect inflorescences. Eperua cerradoensis has a non-tubular corolla, white petals, and exserted stamens, and is most similar to E. duckeana and E. schomburgkiana, from which it differs by the bracteole size and phenology, flower indumentum, besides other vegetative characteristics. Eperua manausensis has a tubular corolla, pink to purple petals, and inserted stamens, and it is most similar to E. grandiflora subsp. guyanensis, but differs from it by the bracteole position and phenology and flower indumentum. The type localities of both species are very unusual: a backyard (E. cerradoensis) and a botanical garden (E. manausensis). The two species have been collected in the last five years. These discoveries show that new undescribed species can be found even in more disturbed areas and that comprehensive knowledge of the flora requires new collections and more taxonomists.